The Role of HRIS (Human Resource Information System) in Improving HR Management Efficiency - Anggoro, Yudhi; Aminullah, A.; Lazuardi, Billy; Setyorini, Efi Endang Dwi; Chin, Jacky (Dinasti Publisher, 2026)
This study examines the role of Human Resource Information Systems (HRIS) in enhancing human resource management efficiency using a quantitative approach. In the context of digital transformation, organizations are required to optimize HR functions through the effective use of integrated information technology. HRIS facilitates the automation of administrative processes, enables real-time data availability, and supports data-driven decision-making. Data were collected from 150 HR practitioners working in various companies in the Greater Jakarta area who had implemented HRIS for at least one year, using purposive sampling. The research instrument was a structured questionnaire measured on a five-point Likert scale, which demonstrated strong validity and reliability, with Cronbach’s Alpha values exceeding 0.87 for all variables. Data analysis was conducted using SPSS version 25 and multiple linear regression after meeting classical assumption tests, including normality, multicollinearity, heteroscedasticity, and autocorrelation. The results indicate that administrative process automation (β = 0.412, p < 0.001), data-driven decision-making (β = 0.358, p < 0.001), and employee productivity improvement (β = 0.287, p < 0.01) have significant positive effects on HR management efficiency, both individually and simultaneously. The coefficient of determination (R² = 0.723) shows that these HRIS dimensions explain 72.3% of the variance in HR management efficiency. Overall, the findings confirm that HRIS implementation enhances HR operational efficiency by reducing processing time, minimizing manual errors, and improving the quality of strategic decision-making. Nevertheless, organizations must address challenges related to implementation costs, system integration, and resistance to change through strategic planning, continuous training, strong top management support, and adequate technological infrastructure.